Numerical simulation and compact modeling of low voltage pentacene based OTFTs - Dwivedi, A.D.D. (H. : ĐHQGHN, 2020)
As organic thin film transistors (OTFTs) are poised to play a key role in flexible and low-cost electronic applications, there is a need of device modeling to support technology optimization and circuit design. This paper demonstrates the technology computer-aided design (TCAD) based numerical simulation, compact modeling and parameter extraction of a low voltage Pentacene based OTFTs. In this paper, fundamental semiconductor equations are tuned up to represent the device electrical characteristics using device numerical simulation. We also present the compact device modeling and parameter extraction of low voltage pentacene based OTFT using the universal organic thin-film transistor (UOTFT) model. Results of finite element method based ATLAS simulation and compact modeling are validated with the experimental results of fabricated Pentacene based OTFT devices. Further, P-type TFT based inverter is also simulated to evaluate the compact model against a simple circuit simulation.